A Synthesis of Systemic Action Research Processes in the CLARISSA Programme on Worst Forms of Child Labour - Burns, Danny; Apgar, Marina (Institute of Development Studies, 2024)
This paper describes, synthesises and analyses the work of 25 Action Research Groups that were the heartbeat of the CLARISSA Systemic Action Research programme. The CLARISSA programme worked to create participatory and systemic solutions to the worst forms of child labour in the adult entertainment sector in Nepal, and the leather sector in Bangladesh. The paper explores how the action research groups were set up, and how they worked through key stages of trust and relationship building, generating evidence, building theories of change, planning and taking action, and assessing the effects of that action. The paper, which is a synthesis of the evidence and learning produced in the programme, draws together learning about the process for both ground-level action researchers and those who might fund, design or implement future programmes.

Reframing, refining, and reconceptualising the worst forms of child labour through participatory adaptive programming - Apgar, Marina; Burns, Danny (Journal of modern slavery, 2021)
This article explores the potential of using participatory action research as an adaptive programming modality to drive learning and innovation to tackle the drivers of (and seek to eliminate) the Worst Forms of Child Labour. We draw on our experience from early phases of implementation of a large-scale action research programme, which despite the constraints covid-19 posed in moving to full implementation and participatory engagement with children and other stakeholders on the ground, is already generating rich learning about the opportunities and challenges of designing programmes that respond to the complex reality of WFCL. We share early learning about what it takes to be fully open to using the lived experience of programme development, and early findings from scoping and mapping of the dynamics of social norms, business practices and urban neighbourhoods and supply chains influencing WFCL in Bangladesh and Nepal, to frame and reframe the questions and response strategies and operationalise a participatory adaptive intent to work with hidden and complex dynamics that characterise the WFCL.

Designing a Participatory Programme at Scale: Phases 1 and 2 of the CLARISSA Programme on Worst Forms of Child Labour - Burns, Danny; Apgar, Marina; Raw, Anna (Institute of Development Studies, 2021)
CLARISSA (Child Labour: Action-Research-Innovation in South and South-Eastern Asia) is a large-scale Participatory Action Research programme which aims to identify, evidence, and promote effective multi-stakeholder action to tackle the drivers of the worst forms of child labour in selected supply chains in Bangladesh, Nepal, and Myanmar. CLARISSA places a particular focus on participants’ own ‘agency’. In other words, participants’ ability to understand the situation they face, and to develop and take actions in response to them. Most of CLARISSA’s participants are children. This document shares the design and overarching methodology of the CLARISSA programme, which was co-developed with all consortium partners during and since the co-generation phase of the programme (September 2018–June 2020). The immediate audience is the CLARISSA programme implementation teams, plus the Foreign, Commonwealth & Development Office (FCDO). This design document is also a useful reference point for other programmes trying to build large-scale participatory processes. It provides a clear overview of the CLARISSA programmatic approach, the design, and how it is being operationalised in context.

Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (Institute of Development Studies, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.
Accepted: 2022-04-25T10:25:54Z

Evaluating CLARISSA: Innovation Driven by a Participatory Learning Agenda - Apgar, Marina; Snijder, Mieke; Kakri, Shanta; Macleod, Shona; Paul, Sukanta; Sambo, Anna; Ton, Giel (Institute of Development Studies, 2020)
Children end up in child labour as a result of many, often unknown or hidden, interactions between multiple actors and multiple factors within households, communities, and labour systems, leading to unpredictable outcomes for children and other sector stakeholders and sometimes resulting in the worst forms of child labour (WFCL). It is a complex problem, and interventions aimed at tackling it are also, inevitably, complex and challenging. The way they influence change is non-linear, causality is uncertain, and unintended consequences may result. Programmes such as the Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) that are engaging with such intractable challenges and aim to reach the most left behind (children in WFCL) are operating in conditions of complexity. This complexity poses significant challenges to the way programmes are designed, planned, implemented, and evaluated, and requires a move away from linear and predetermined models. In this Working Paper, we share our experience and early learning about how to design and implement monitoring, evaluation and learning that intentionally embraces the challenge of complexity.
Accepted: 2020-06-25T14:55:41Z

Designing Contribution Analysis of Participatory Programming to Tackle the Worst Forms of Child Labour - Apgar, Marina; Snijder, Mieke; Prieto Martin, Pedro; Ton, Giel; Macleod, Shona; Kakri, Shanta; Paul, Sukanta (Institute of Development Studies, 2022)
This Research and Evidence Paper presents the theory-based and participatory evaluation design of the Child Labour: Action-Research- Innovation in South and South-Eastern Asia (CLARISSA) programme. The evaluation is embedded in emergent Participatory Action Research with children and other stakeholders to address the drivers of the worst forms of child labour (WFCL). The report describes the use of contribution analysis as an overarching approach, with its emphasis on crafting, nesting and iteratively reflecting on causal theories of change. It illustrates how hierarchically-nested impact pathways lead to specific evaluation questions and mixing different evaluation methods in response to these questions, critical assumptions, and agreement on causal mechanisms to be examined in depth. It also illustrates how realist evaluation can be combined with contribution analysis to deeply investigate specific causal links in the theory of change. It reflects on learning from the use of causal hotspots as a vehicle for mixing methods. It offers considerations on how to navigate relationships and operational trade-offs in making methodological choices to build robust and credible evidence on how, for whom, and under what conditions participatory programming can work to address complex problems such as child labour.
Accepted: 2022-08-18T11:05:51Z

Bridging Learning and Action: How Did CLARISSA’s Participatory Adaptive Management Approach Foster Innovation, Effectiveness, and Stakeholder Empowerment? - Prieto Martin, Pedro; Apgar, Marina; Afroze, Jiniya; Arulanantham, Amit; Hicks, Jacqueline; Karki, Shanta; Mareschal, Sophie; Paul, Sukanta; Snijder, Mieke; Uddin, Forhad; Veitch, Helen (Institute of Development Studies, 2024)
Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) is an evidence and innovation-generation programme funded by the United Kingdom’s Foreign, Commonwealth & Development Office (FCDO), responding to the challenge of the worst forms of child labour (WFCL) in Bangladesh and Nepal. It is a challenge characterised by a poor understanding of its drivers and a lack of evidence on what works to combat it. To handle such fundamental uncertainty, the programme adopts a child-centric and participatory action research approach, which is supported by an adaptive management model to respond better to challenges and opportunities. From its inception, the programme needed to navigate shocks and challenges, such as Covid-19 lockdowns, political upheaval, and sustained budget cuts, which put its capacity to learn and evolve to the test. This paper shares insights emerging from evaluating CLARISSA’s participatory adaptive management (PAM) practices, connecting them with current discussions on adaptive management. It provides an in-depth evaluation of CLARISSA’s PAM approach, exploring how adaptive strategies were implemented and evolved throughout the programme’s life cycle. Multiple cases of adaptation and misadaptation were selected and analysed through a series of in-depth interviews and review of programme documentation, allowing us to assess whether and how the adaptive management practices have been operationalised, the degree to which they led to enhanced decision-making and effectiveness, and their empowering effect on children and other programme stakeholders. Through conceptual analysis and real-world examples, the paper examines the key stages and critical dimensions of PAM, conveying the complexities and dynamism of adaptive management in development work, while highlighting both the successes and challenges encountered in operationalising PAM within CLARISSA.
Accepted: 2024-05-10T08:21:46Z